A conceptual framework that monitors port facility access through integrated Port Community Systems and improves port and terminal security performance. (11th June 2020) - Koliousis, Ioannis
Ports and terminals are considered critical infrastructure with higher protection requirements for an effective and efficient operation. This research introduces a security enhancement architectural framework for the specific case of port and port terminal facilities' passenger traffic, combining two different attributes, the cyber and the physical, and operationally integrating the proposed subsystem to the Port Community System. More precisely, this paper identifies, introduces and analyses a system that supports risk management by developing and validating a security framework which is based on monitoring access through automated border control (ABC) structures aimed at ports and terminals. Additionally, the modular prototype developed, enhances the information sharing capabilities of the Port Community Systems in a way that improves collaboration for security related procedures, based on existing and easy to develop software capabilities. The architectural framework is validated by domain experts through semi-structured interview workshop improving the robustness of the top-down model for the design and the implementation of a risk management approach based on improved communication sharing and utilising advanced equipment.